Difference in agility, strength, and flexibility in competitive figure skaters based on level of expertise and skating discipline - Slater, L. V.; Vriner, M.; Zapalo, P.; Arbour, K.; Hart, J. M. (The Journal of Strength and Conditioning Research, 2016)
Figure skating is an extremely difficult sport that requires a combination of grace, artistry, flexibility, speed, and power. Although many skaters are involved with strength and conditioning programs, there is no current information about differences in off-ice performance measures based on skating discipline and level. The purpose of this study was to compare agility, strength, and flexibility performance based on skating discipline and level. A total of 343 figure skaters from 4 different disciplines (singles, dance, pair, and synchronized skating) and 3 different levels (novice, junior, and senior) completed combine testing with the United States Figure Skating Association. All subjects completed the hexagon agility test, t-test, triple bound jumps, vertical jump, timed tuck jumps, push-ups, v-ups, hand press, front split, seated reach, and stork pose. A multivariate analysis of variance with Scheffe's post hoc was used to identify differences in performance based on skating discipline and level. Mean differences, Cohen's d effect sizes, and 95% confidence intervals were reported for all significant differences. Senior and junior skaters tended to be faster and stronger than novice skaters. Singles, dance, and pair skaters tended to be more agile, stronger, and flexible than synchronized skaters, however, senior synchronized skaters tended to perform better than senior skaters in other disciplines. These results indicate that strength and conditioning professionals should consider skating discipline and level when designing strengthening programs for figure skaters.